The Influence of Corporate Social Responsibility on Tax Avoidance - Fransisco Pandapotan (Journal of Applied Business, Taxation and Economics Research, 2023)
Tax avoidance is an action to minimize the tax expense because tax is a burden which reduces profits. This research is conducted to investigate how corporate social responsibility affects on tax avoidance empirically. This is classified as causal research with quantitative approach. The population used in this research is all consumer goods manufacturing companies which are registered in Indonesia Stock Exchange period 2019-2020 with a purposive sampling technique to obtain 49 samples after outliers. All of the data samples were taken from the annual reports and financial statements. Multiple linear regression analysis is used to test the effect of corporate social responsibility on tax avoidance using the SPSS version 22. The result of this research shows that corporate social responsibility positively and significantly affects tax avoidance.